Ecology and evolution of mountain butterflies - Klečková, Irena (Jihočeská univerzita, 2014)
The thesis deals with speciation processes, thermal ecology and habitat use in Holarctic mountain and arctic butterflies. It demonstrates a crucial role of environmental heterogeneity for speciation, survival of butterfly lineages, coexistence of closely related species and, finally, for resource use of sexes with different habitats demands at the level of individual species.
Ecology and evolution of mountain butterflies
Keywords: ecology; evolution; butterflies; behavioural thermoregulation; management; Erebia; Oeneis; ecology; evolution; butterflies; behavioural thermoregulation; management; Erebia; Oeneis